Tinjauan Yuridis Kredit Tanpa Agunan Di Bank Bpr Ukabima Bmms Jogonalan (Studi Kasus Di Klaten) - Prabowosiwi, Muhammad; , Septarina Budiwati, S.H., M.H (2016)
Purpose of the research is to know legal construction of unsecured loan agreement, emerging problems, and settlement procedure of the agreement in BPR UKABIMA BMMS Jogonalan. The research is descriptive one with juridical empiric method. Data of the research consists of primary data collected by using interview and secondary data, namely primary data of law and secondary data. The data was collected by using observation and interview and the data was analyzed qualitatively. Results of the research indicated that the unsecured loan agreement was providing a loan only if it was applied in written. Problems emerging from the unsecured loan agreement were technical problems and substance problems that emerging from disharmony between Act No. 10 of 1998 on Banking and President Instruction No. 5 of 2008, and the third problem was coming from knowledge of debtor. And, if there are problem loans, the bank had procedure to settle it, namely by using peaceful persuasive meeting of the two parties to obtain mutual agreement.